2022
DOI: 10.1093/ehjcr/ytac006
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Mechanical mitral prosthetic valve thrombosis in the context of COVID-19 despite effective anticoagulation

Abstract: Background The SARS-CoV2 virus has been an emerging virus since December 2019 and is the cause of a global pandemic whose clinical manifestations extend far beyond respiratory disease. Case summary A patient with severe COVID 19 respiratory infection, carrying a mechanical mitral valve and under anticoagulation, was admitted in our cardiology department because of a new atrial fibrillation, which turned out to be related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The eight COVID-19-related PVT cases documented in this paper include valve type (mitral versus aortic) and prosthesis type (bioprosthetic versus mechanical). Of these cases, five involved prostheses in the mitral valve position, three of which were mechanical [ 5 7 ] and two were bioprosthetic [ 8 , 9 ]; three of the eight cases involved aortic valve prostheses, one being mechanical [ 10 ] and two being surgical bioprosthetic valves [ 11 , 12 ] (Table 1 ). Seven of eight patients had symptoms of dyspnea or hypoxia [ 5 9 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The eight COVID-19-related PVT cases documented in this paper include valve type (mitral versus aortic) and prosthesis type (bioprosthetic versus mechanical). Of these cases, five involved prostheses in the mitral valve position, three of which were mechanical [ 5 7 ] and two were bioprosthetic [ 8 , 9 ]; three of the eight cases involved aortic valve prostheses, one being mechanical [ 10 ] and two being surgical bioprosthetic valves [ 11 , 12 ] (Table 1 ). Seven of eight patients had symptoms of dyspnea or hypoxia [ 5 9 , 11 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these cases, five involved prostheses in the mitral valve position, three of which were mechanical [ 5 7 ] and two were bioprosthetic [ 8 , 9 ]; three of the eight cases involved aortic valve prostheses, one being mechanical [ 10 ] and two being surgical bioprosthetic valves [ 11 , 12 ] (Table 1 ). Seven of eight patients had symptoms of dyspnea or hypoxia [ 5 9 , 11 , 12 ]. Al Helali et al presented a patient with a mechanical aortic valve prosthesis presenting with a change in character of cardiac auscultation and generalized fatigue [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also suggested that elevated levels of neutrophil extracellular traps are closely related to thrombotic events ( Zuo et al, 2021 ), but their overall role in COVID-19-related thrombosis remains unclear ( Bonaventura et al, 2021 ). At present, most reports on thrombosis in patients with COVID-19 are case reports ( Achim et al, 2022 ; Bleiziffer et al, 2022 ; Jeckelmann et al, 2022 ; Russell et al, 2022 ; Takasu et al, 2022 ) and some observational studies ( Maier et al, 2020 ). Even after strict ethical review, only a small number of large studies have confirmed the relationship between the use of anticoagulants and the survival rate of COVID-19 ( Lawler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%